A 200mV 32b Subthreshold Processor with Adaptive Supply Voltage Control - Luetkemeier, Sven; Jungeblut, Thorsten; Porrmann, Mario; Rückert, Ulrich (Proc. IEEE Int. Solid-State Circuits Conf. Digest of Technical Papers)
In recent years, subthreshold operation has become a research focus for digital systems with limited energy budget (e.g. mobile, battery-powered devices, radio frequency identification (RFID), wireless sensor networks, or biomedical applications). Subthreshold operation allows for such low power consumption by reducing the supply voltage of the circuit below the threshold voltage of the transistors. As dynamic power depends quadratically on supply voltage, and static power depends exponentially on supply voltage, considerable power savings are achieved. At the same time propagation delays increase due to reduced transistor currents. Effectively, energy consumption per cycle can typically be reduced by a factor of 10 using subthreshold operation.

A 245 GHz CB LNA and SHM mixer in SiGe technology - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (SiRF 2012 (Silicon Monolithic Integrated Circuits in RF Systems))
The paper presents a four stage 245 GHz LNA in an f t /f max =280/425 GHz SiGe technology and a 4 th sub harmonic 245 GHz transconductance mixer in an f t /f max =250/300 GHz SiGe technology. The LNA takes advantage of common base (CB) topology for each stage and has 12 dB gain at 245 GHz, while exhibiting a 3 dB bandwidth of 26 GHz. It has a supply voltage of 2V and power dissipation of 28 mW. The transconductance mixer has -7 dB conversion gain at 245 GHz with an LO power of 8 dBm at 61 GHz. The mixer draws 9.8 mA at 3V. Simulation results of the receiver comprising the CB LNA and SHM mixer are given.

Deployment of mobile routers ensuring coverage and connectivity - Mathews, Emi; Mathew, Ciby (International Journal of Computer Networks and Communications 4(1))

Lesetexte besser verstehen - Lesestrategien erlernen und den Wortschatz erweitern - Hellmich, Frank; Hoya, Fabian Karl; Förster , Sabrina (Deutsch Differenziert)

Rezension: Handbuch Grundschulpädagogik und Grundschuldidaktik - Hellmich, Frank (Zeitschrift für Grundschulforschung)

Förderung der Lesekompetenz durch ein wortschatzbasiertes Lesestrategietraining bei Kindern mit Deutsch als Zweitsprache - Förster, Sabrina; Niebuhr-Siebert, Sandra; Hellmich, Frank (Bedingungen des Lehrens und Lernens in der Grundschule. Bilanz und Perspektiven)

Professional competence and intuitive decision making: A simulation study in the domain of emergency medicine - Harteis, Christian; Morgenthaler, Barbara; Kugler, Christine; Ittner, Karl-Peter; Roth, Gabriel; Graf, Bernhard (Vocations and Learning)

When workplace learning fails: Individual and organisational limitations--Exemplarily demonstrated by the issue of responsibility in work life - Harteis, Christian (International Journal of Human Resources Development and Management)

Human fallibility and learning from errors at work - Bauer, Johannes; Gartmeier, Martin; Harteis, Christian (Human fallibility)

The ambiguity of errors for work and learning: Introduction to the volume - Bauer, Johannes; Harteis, Christian (Human Fallibility)

Research on human fallibility and learning from errors at work: Challenges for theory, research, and practice - Harteis, Christian; Bauer, Johannes; Heid, Helmut (Human Fallibility)

Error Orientation in the Context of Intuitive and Competent Behaviour: Results of an Exploratory Study in the Domain of Emergency Medicine - Harteis, Christian; Frost, Franziska (Human Fallibility)

LehreProfi--Entwicklung und Einsatz eines Instruments zur Erfassung hochschuldidaktischer Kompetenz - Fiehn, Janina; Spieß, Stefan; Ceylan, Firat; Harteis, Christian; Schworm, Silke (Lernwelt Universität)

Human fallibility: The ambiguity of errors for work and learning

Entwicklungsaufgaben im Erwachsenenalter - Gruber, Hans; Harteis, Christian (Handbuch Professionsentwicklung)

Learning from errors in the professions - Bauer, Johannes; Gartmeier, Martin; Harteis, Christian (Human fallibility. The ambiguity of errors for work and learning)

Wuttke & Seifried (Eds.). (2012). Learning from errors at school and at work - Buschmeyer, Katrin; Harteis, Christian (Vocations and Learning. Studies in Vocational and Professional Education)

Learning from mistakes - still a challenge for research and business practice - Harteis, Christian; Buschmeyer, Katrin (Learning from errors at school and at work)

Error orientation and intuitive decision making - Harteis, Christian; Frost, Franziska (Human fallibility. The ambiguity of errors for work and learning)

Jahrbuch Medienpädagogik 9. Qualitätsentwicklung in der Schule und medienpädagogische Professionalisierung